Morphological aspects of the digestive system in freshwater stingray (Potamotrygon amandae—Loboda and Carvalho, 2013): myliobatiformes; potamotrygoninae - de Aquino, Júlia Bastos; de Melo, Luana Felix; Rodrigues, Rosângela Felipe [UNESP]; de Melo, Alan Peres Ferraz [UNESP]; de Morais-Pinto, Luciano [UNESP]; Rici, Rose Eli Grassi [UNESP] (Springer Nature, 2023)
Detailed morphological descriptions supported by macroscopic, microscopic and ultrastructural analyses of the complete digestive system of the Potamotrygon amandae from the Brazilian Amazon basin were used in this study. For this purpose, six healthy adult specimens were dissected and had samples from all segments of the digestive system fixed and processed according to protocol for light and scanning electron microscopy. According to our data, in comparison with other studies in different species of oceanic and freshwater rays, it was possible to observe several morphological similarities in cell and tissue arrangement, in addition to the similarity of shape and topographic position of the organs. Thus, it was possible to conclude that the morphological and cytoarchitectural similarity is phylogenetically maintained according to a succession of functionally successful processes in the evolutionary history of the taxon. Furthermore, the minor morphological variations observed in Potamotrygon amandae may be related to habitat and diet specificity.
Keywords: Amazonian fishes; Animal anatomy; Digestive tract; Elasmobranchs